METHODOLOGICAL BASIS FOR THE FORMATION OF PRIORITIES FOR THE DEVELOPMENT OF THE COX-CHEMICAL INDUSTRY OF UKRAINE WITH THE APPLICATION COGNITIVE TECHNOLOGIES (Economic journal of Lesya Ukrainka Volyn National University, 2023)
Introduction. The article states that the domestic coke industry is of strategic importance for the economy. But today it works in difficult conditions and faces significant problems, which affects the reduction of production. Effective activity of the industry is possible only under the conditions of a systemic vision of its development, which involves the formation of appropriate priorities that take into account modern challenges, as well as weak controllability, uncertainty and variability of the external environment. This specificity limits the use of classical economic and mathematical methods and models.The purpose of the article is to develop a methodical approach to the formation of strategic priorities for the development of the coke-chemical industry of Ukraine using cognitive modeling methods.Results. The paper proves the effectiveness of cognitive modeling and the related scenario, which is due to the possibility of directing the activity of complex objects in poorly structured problem situations that arise during the functioning of enterprises in the industry. A methodical approach to justifying the development priorities of the domestic coke industry based on the application of cognitive technologies is proposed. It is based on scenario modeling using cognitive maps. Implementation of a set of analytical and calculation actions is foreseen. Among its main stages, the following are distinguished: analysis of regulatory influence factors, the strength of the connection between them, identification of trends that can affect the work of the coke chemical industry; construction of a cognitive model of factors of regulatory influence on the activity of the industry (a cognitive map in the form of an indicative graph); implementation of scenario modeling and formation of industry development scenarios and forecasts that take into account the dynamics of processes over time.Conclusiоns. This methodological approach is aimed at obtaining results that should form the basis for adjusting the strategic priorities of the development of the coke-chemical industry of Ukraine.
Keywords: coke industry, development, priorities, cognitive modeling, national economy, economic methods, efficiency.